Serological monitoring of vaccine immunity to diphtheria, tetanus and pertussis in the population of Kharkiv city and region in 2025 - Smilyanskaya, Maya; Volianskyi, Andriy; Didorenko, Tatiana; Karlova, Tatiana; Lysenko, Oleh (Annals of Mechnikov's Institute, 2025)
Morbidity and mortality from infections and non-communicable chronic somatic diseases require constant improvement in vaccine prevention. This is dictated by the steady increase in the number of cases among vaccinated people, the increase in the frequency of childhood infections in people over 18 years of age, the increase in the number of complications after diseases, the rapid fading of vaccine-induced immunity with age, high mortality and the development of complications leading to disability, in particular with influenza and pneumococcal pneumonia, and the difficulty of creating intense immunity in the elderly. Effective control of infections requires the actual achievement of protection against them in more than 95% of the population. Weak immunity and lack of protection against infectious diseases create a niche for the circulation of pathogens and are a source of epidemic and pandemic development. The response to an associated vaccine is much more complex, and after the introduction of such a vaccine into the body, antibodies are formed against an even greater number of antigenic determinants. The creation of persistent immunity to infections depends not only on the quality of the vaccines used, but, to a greater extent, on the immunoreactivity of patients. Materials and methods. The work was performed in the laboratory of immunorehabilitology of the Mechnikov Institute of Microbiology and Immunology. Studies to determine the level of specific immunity of the population of Kharkiv and the region to vaccine-preventable infectious diseases were performed using cross-sectional epidemiological analysis. The sample size was established in accordance with the WHO recommendations and the EPI INFO-2000 program and included 535 people aged 0–60 years. The inclusion and exclusion criteria for individuals in the study were as follows: absence of immunosuppression, malignant neoplasms, or severe hematological diseases. This study was conducted in accordance with the Declaration of Helsinki and the principles of Good Clinical Practice. Participants or their parents were provided with information about the objectives of the study, and written informed consent was obtained from all participants or their parents prior to inclusion in the study. All individuals included in the study completed appropriate questionnaires and blood serum was collected. The levels of specific antibodies to diphtheria, tetanus, and pertussis pathogens/toxins were determined using reagent kits from IBL-Hamburg GmbH (Germany) by the standard method, according to the manufacturer's instructions. The studies were performed using a multistrip photometer for ELISA Erba LisaScan, by a quantitative method (units of measurement – IU/ml). Following the recommendations proposed by the manufacturer, antibody levels were evaluated as follows: anti-pertussis: below 16 IU/ml – no immunity, 16–24 IU/ml – weak immunity, above 24 IU/ml – sufficient immunity; anti-diphtheria and anti-tetanus: below 0.1 IU/ml – no immunity, 0.1–1.0 IU/ml – weak immunity, above 1.0 IU/ml – sufficient immunity. Results and discussion. Most of the adults we examined had protective antibody titers against diphtheria and tetanus. A significant proportion of them had high antibody titers, indicating the presence of strong immunity. The results obtained indicate a high level of anti-diphtheria and anti-tetanus immunity, which can be considered a result of adult population revaccination against these infections. On the contrary, most of the adults we examined had low titers of anti-pertussis antibodies. The average IgG titers of anti-pertussis antibodies in adults were significantly lower than those in the vaccinated younger children we examined, which indicates the need to develop vaccination programs for adolescents and adults. Martial law, complications of modern vaccination schedules, migration, and population aging, as well as refusal to vaccinate for various reasons, lead to the need to implement in Ukraine a separate system of monitoring the specific serological profile at the population level, which allows for the assessment of the landscape of protection against infections in modern society and identifying those susceptible to infections. Its implementation will allow clarification of the true values of collective immunity in different social groups and regions, better management of the vaccination schedule, assessment of the effectiveness of vaccines and vaccination programs, and will also allow calculation of the required volume of vaccines, diagnostic and medicinal products, as well as the resources necessary to ensure full protection of the population.